2013
DOI: 10.12968/bjon.2013.22.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours and attitudes towards being role models

Abstract: Nurses are often viewed by the general public as role models for health. This study investigated health behaviours in pre-registered nurses and their attitudes towards being role models to their patients. In total, 540 pre-registered nurses self-reported their level of physical activity, smoking habits, alcohol intake and dietary habits.Overall, 24% were overweight or obese, 47% were not physically active enough to benefit their health, 73% did not eat the recommended five portions of fruit and vegetables per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
121
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 27 publications
17
121
0
3
Order By: Relevance
“…This confirms the findings of Naidoo et al, who reported poor physical activity levels among nurses in South Africa (11). These findings are supported by other studies that found that nurses do not meet the recommended levels of physical activity required for health benefit (12). Our study showed that the majority of participants ate semi-healthy food; some ate unhealthy food such as processed meat, sweets, caffeinated beverages, and meat or poultry with skin; and others ate healthy food like fruit and vegetables.…”
Section: Discussionsupporting
confidence: 91%
“…This confirms the findings of Naidoo et al, who reported poor physical activity levels among nurses in South Africa (11). These findings are supported by other studies that found that nurses do not meet the recommended levels of physical activity required for health benefit (12). Our study showed that the majority of participants ate semi-healthy food; some ate unhealthy food such as processed meat, sweets, caffeinated beverages, and meat or poultry with skin; and others ate healthy food like fruit and vegetables.…”
Section: Discussionsupporting
confidence: 91%
“…Although most nurses did not feel under particular pressure to be perfect role models, there was a prevailing attitude that nurses in general should be role models for health, and should engage in positive lifestyle behaviours themselves. This is consistent with the attitudes of preregistered nurses in all fields of nursing (Chalmers et al, 2002;Blake and Harrison, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…The authors do not have any information on the health behaviours, attitudes or beliefs of non-respondents and the response rate was low (perhaps due to data being collected around the time of a largescale trust staff survey). However, the sample was relatively representative of the paediatric nurse population at the participating hospital trust and reported opinions are consistent with those found in other nursing samples (Blake and Harrison, 2013).…”
Section: Limitationssupporting
confidence: 78%
See 2 more Smart Citations